Answer 1
x= -(2/ 7)
Explanation:
Y=-2x+6 ---(equation 1)
3y-x+3=23 ------ (equation 2)
There are two unknowns in both the equation.
First substitute the value of y in equation 2:
3(-2x +6) - x +3 = 23
multiply the number outside the bracket with the number inside the bracket:
-6x + 18 - x + 3 = 23
Take all the x terms first:
-6x - x + 18 +3 = 23
-7x +21 = 23
-7x = 23-21
-7x = 2
x = -(2 / 7)
Answer 2
y= 46 / 7
Explanation:
Following the same steps to find the value of y
Y=-2x+6 ---(equation 1)
3y-x+3=23 ------ (equation 2)
There are two unknowns in both the equation.
First substitute the value of y in equation 2:
3(-2x +6) - x +3 = 23
multiply the number outside the bracket with the number inside the bracket:
-6x + 18 - x + 3 = 23
Now to find the value of y, put the value of x from answer 1 into equation to find y:
y= -2 × -(2 / 7) + 6
y= 4/7 +6
y= 46 / 7